Konflik Peran Ganda Ditinjau daro Fear of Success pada Wanita yang Bekerja - Zuraida, Zuraida (Jurnal Ilmiah Psyche, 2020)
Women who work and are married have a dual role conflict, this causes a fear of women to succeed in a working (fear of success). This study aims to examine the relationship of dual role conflict with fear of success in working women. Dual role conflict variables and fear of success are measured using a scale. The subjects of this study were 120 working women with accidental sampling. The analysis technique used in this study is quantitative analysis using correlation product moment karl pearson analysis (SPSS Version 20 for Windows). Based on the results of the study, it is known that dual role conflict has a positive relationship with fear of success in women who work. There is a significant positive correlation (r0.736 with sig <0.05) between the dual role conflict variable and the fear of success in women who work at 0,000 and the significance value is below / smaller than 0.05. this means that the higher the dual role conflict, the higher the fear of success in women who work and vice versa the lower the dual role conflict, the lower the fear of success in women who work. In the dual role conflict has the most moderate level category with a contribution of 55.84% and the most fear of success has a medium level category with a contribution of 45%.